Advances in Pharmacokinetic Modelling and Computational Approaches for Nanoparticles in Drug Delivery Systems - Dhoundiyal, Shivang; Alam, Md A. (Recent Advances in Drug Delivery and Formulation, 2023)
Generally, therapeutic drugs have issues like poor solubility, rapid removal from the bloodstream, lack of targeting, and an inability to translocate across cell membranes. Some of these barriers can be overcome by using nano drug delivery systems (DDS), which results in more efficient drug delivery to the site of action. Due to their potential application as drug delivery systems, nanoparticles are the main topic of discussion in this article. Experimental and computational investigations have substantially aided in the understanding of how nanocarriers work and how they interact with medications, biomembranes and other biological components. This review explores how computational modelling can aid in the rational design of DDS that has been optimized and improved upon. The most commonly used simulation methods for studying DDS and some of the most important biophysical elements of DDS are also discussed. Then, we conclude by investigating the computational properties of various types of nanocarriers, such as dendrimers and dendrons, polymer-, peptide-, nucleic acid-, lipid-, carbon-based DDS, and gold nanoparticles.
Keywords: molecular dynamics